The global burden of aortic aneurysm in adults over 55: evolving trends, risk factors, and projections - Ma, Guoqian; Li, Yuan; Jia, Fan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAortic aneurysm (AA) is a life-threatening vascular disease and a major contributor to global cardiovascular mortality, particularly in older adults. This study aims to report global trends in mortality and disability-adjusted life years (DALYs) attributable to AA among adults aged 55 years and older from 1990 to 2021.MethodsWe conducted a comprehensive analysis of aortic aneurysm mortality and disability-adjusted life years (DALYs) from 1990 to 2021, utilizing data from the Global Burden of Disease (GBD) study. Trends were examined by sex, age group, socio-demographic index (SDI), region, and country. Joinpoint regression was used to assess annual percentage changes (APCs), and Bayesian age-period-cohort (BAPC) modeling projected AA burden to 2035. Primary risk factors were also analyzed.ResultsBetween 1990 and 2021, global AA-related deaths rose by 73.9% [from 79,608 (95% UI, 74,398–84,032) to 138,450 (123,754–149,214)], while the mortality rate declined by 21.4% (from 11.86 to 9.32 per 100,000). Similar patterns were observed for DALYs, with a 62.6% increase in total DALYs but a 26.5% decrease in rates. Males and older adults experienced disproportionately higher mortality and DALY rates. Marked regional and national disparities emerged: the greatest increases in AA burden were seen in low-middle SDI regions [mortality rate EAPC, 1.49 [95% CI, 1.43–1.54]; DALY rate EAPC, 1.29 [95% CI, 1.23–1.35]], while high-income North America and Australasia achieved the largest reductions. The leading risk factor globally was smoking, particularly among males. BAPC projections indicate continued declines in age-standardized AA mortality and DALY rates through 2035, though absolute numbers will likely remain high.InterpretationAlthough rates of AA-related mortality and DALYs have declined globally, the absolute burden continues to rise, driven by population aging and persistent risk factors. Disparities across regions and SDI groups highlight the urgent need for targeted prevention, including tobacco control, risk factor management, and selective screening—especially in rapidly aging, low-resource settings. Strengthening health system capacity for both prevention and surgical intervention will be critical to curbing future AA burden.